La inclusión socioeducativa de personas con discapacidad desde el punto de vista humano y profesional - Naranjo-Pinela, Teresa (Ciencia UNEMI, 2016)
In this paper, which is the result of a qualitative, descriptive and analytical research, it is aimed to demonstrate the importance of inclusive education and the rights of the disabled people, the space they should be offered in society and the role that teachers must face. Given the changes in educational models, their objectives should be framed in the real practice of respect towards people for their simple human condition and intended to publicize the need to apply in an integrated way the inclusive education and thus privileging human part in educational processes. Teachers must be aware of the importance of proper management of a number of methodologies and strategies related to disabled people and their state of vulnerability in order to consider the inclusion, equality and equity in their work area. Inclusive practice needs of a society where there is no difference whatsoever, that people with disabilities have the same opportunities as others to achieve their goals and objectives, this would allow their personal and social development.